Application of high temperature electronics packaging technology to signal conditioning and processing circuits - Riches, S; Cannon, K; Johnston, C; Sousa, M; Grant, P; Gulliver, J; Langley, M; Pittson, R; Serban, S; Baghurst, D; Firmstone, M (2010)
The requirement to install electronic power and control systems in high temperature environments has posed a challenge to the traditional limit of 125°C for high temperature exposure of electronics systems. The leap in operating temperature to above 200°C in combination with high pressures, vibrations and potentially corrosive environments means that different semiconductors, passives, circuit boards and assembly processes will be needed to fulfil the target performance specifications. Bare die mounted onto ceramic and insulated metal substrates can withstand higher temperatures than soldered surface mount devices on printed circuit boards. The results of the evaluation of electronic interconnect and substrate materials that have been submitted to temperatures of 250°C for up to 2000 hours will be presented, including details on novel adhesive formulations and high temperature insulated metal substrates. The materials and processes developed have been applied to the manufacture of high temperature circuits representative of analogue signal conditioning and processing, using silicon on insulator devices and passive components mounted into HTCC packages and onto thick film on ceramic substrates. Results of the characterisation of these devices and circuits at temperatures of 250°C for up to 2000 hours will be presented. This work forms part of the UPTEMP project has been set-up with support from UK Technology Strategy Board and the EPSRC, which started in March 2007 with 3 years duration. The project brings together a consortium of end-users (Sondex Wireline and Vibro-Meter UK), electronic module manufacturers (GE Aviation Systems Newmarket) and material suppliers (Gwent Electronic Materials and Thermastrate Ltd) with Oxford University - Materials Department, the leading UK high temperature electronics research centre.